The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4028/www.scientific.net/amr.139-141.55
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Drilling-Induced Delamination of CFRP with Infiltration Method

Abstract: Carbon fiber reinforced plastics (CFRP) are typical difficult-to-cut materials because of their anisotropic mechanical properties and poor heat conductivity. Drilling is the most common process in the manufacturing of CFRP products in which delamination is the most potentially damaging defect. In the present work the delamination damage around drilled hole of multi-directional CFRP is analyzed by means of infiltration inspection method with gold chloride solution, and the effects of drill rotational rate and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…With the drill entering in the specimen, the thrust rises up to the largest value rapidly [3]. This is verified repeatedly by experiments: if no support pad is used underneath the specimen, there is not enough resistance to the thrust when the last several laminas are drilled (though the thrust is little less at that time), so the drilled composite would form delamination near the exit [9].…”
Section: Delamination Splitting and Its Mechanismmentioning
confidence: 91%
“…With the drill entering in the specimen, the thrust rises up to the largest value rapidly [3]. This is verified repeatedly by experiments: if no support pad is used underneath the specimen, there is not enough resistance to the thrust when the last several laminas are drilled (though the thrust is little less at that time), so the drilled composite would form delamination near the exit [9].…”
Section: Delamination Splitting and Its Mechanismmentioning
confidence: 91%
“…14. A similar method was used by the pioneer researchers in previous works [46,49,65,66]. Three different weights % of graphene oxide were used for the comparative study of machined quality a different case of the same C-scan analysis of drilled hole [46,50].…”
Section: Confirmatory Testmentioning
confidence: 99%
“…They revealed that feed rate, followed by spindle speed, has the greatest impact on thrust force and delamination factor. Quan et al [20] examined the effects of drill speed and feed and the geometry of the drilling hole on delamination at the drill hole using an infiltration method with gold chloride solution. The findings found that the closer to the entry or exit of the hole, the more damaged.…”
Section: Introductionmentioning
confidence: 99%